A quantitative analysis of the chlorination of samarium sesquioxide - Esquivel, Marcelo Ricardo Oscar (2005)
In this work, the experimental data of the chlorination of Sm2O3 analyzed previously by thermogravimetry (TG) between 200 and 350 °C is fitted using the equations of Johnson–Mehl–Avrami (JMA). The presence of a change of the apparent activation energy (Eap) is correlated to a change on the parameters (n and k) of the JMA model. The values of n found were 1/2 and 2/3 in the 200–270 and 270–350 °C, respectively. These values were correlated to a change on the mechanism of the reaction. The k values obtained from the JMA equations were used to confirm the experimental Eap values previously found in the mentioned higher and lower temperature range: 45 ± 5 and 130 ± 5 kJ mol−1, respectively. The nucleation and growth processes observed were also in agreement with results obtained by scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS) and X-ray diffraction (XRD).